3D analysis of thermal and stress evolution during laser cladding of bioactive glass coatings. (June 2016) - Krzyzanowski, Michal; Bajda, Szymon; Liu, Yijun; Triantaphyllou, Andrew; Mark Rainforth, W.; Glendenning, Malcolm
Abstract: Thermal and strain–stress transient fields during laser cladding of bioactive glass coatings on the Ti6Al4V alloy basement were numerically calculated and analysed. Conditions leading to micro-cracking susceptibility of the coating have been investigated using the finite element based modelling supported by experimental results of microscopic investigation of the sample coatings. Consecutive temperature and stress peaks are developed within the cladded material as a result of the laser beam moving along the complex trajectory, which can lead to micro-cracking. The preheated to 500 °C base plate allowed for decrease of the laser power and lowering of the cooling speed between the consecutive temperature peaks contributing in such way to achievement of lower cracking susceptibility. The cooling rate during cladding of the second and the third layer was lower than during cladding of the first one, in such way, contributing towards improvement of cracking resistance of the subsequent layers due to progressive accumulation of heat over the process.